Q: What is the anti-derivative of x squared plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

sqrt(1) + 3*sqrt(x) = 1 + 3*x^1/2So the antiderivative is x + [3*x^(3/2)]/(3/2) + c = x + 2*x^(3/2) + c where c is the constant of integration.

(x + 3)(x + 3)

x + 5

Asuming it starts "x squared" the the answer is (x-3)(x-3) or (x - 3)squared

(x + 3)(x + 2)

Related questions

sqrt(1) + 3*sqrt(x) = 1 + 3*x^1/2So the antiderivative is x + [3*x^(3/2)]/(3/2) + c = x + 2*x^(3/2) + c where c is the constant of integration.

(x + 3)(x + 3)

If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3

x + 3

x + 5

Asuming it starts "x squared" the the answer is (x-3)(x-3) or (x - 3)squared

Let k = 0 9x18 squared x 17 x 18 k is a constant. Its anti-derivative is kx + C, where C is a constant. The anti-derivative squared is (kx+ C) squared.

It is (x+3)(x+4) when factored

(x + 3)(x + 2)

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

x2 + 4x + 3 =(x + 3) (x + 1)

(2/3)*x^(3/2)